3D CFD modeling of natural draft wet-cooling tower with flue gas injection. (5th December 2015) - Klimanek, Adam; Cedzich, Michał; Białecki, Ryszard
Abstract: The paper presents a study on numerical modeling of a natural draft wet-cooling tower with flue gas injection. A previously developed 3D CFD model of a natural draft wet-cooling tower is adopted to account for the flue gas injection. The model is validated against experimental data and then applied to verify the effect of flue gas injection on the cooling tower performance. The effect of wind speed on the rising plume and injected gas is also studied. It is concluded that the injected flue gas has insignificant influence on the cooled water temperature. The increasing wind speed is a reason of recirculation regions formation near the tower outlet which leads to flue gas flow near the tower shell increasing the risk of corrosion. Graphical abstract: Highlights: We developed a CFD model of a natural draft cooling tower with flue gas injection. The model was validated against experimental data. Influence of flue gas injection on tower performance was examined. The effect of crosswind on plume and tower performance was studied. Increased risk of tower shell corrosion under crosswind was observed.